A porous and redox active ferrocenedicarboxylic acid based aluminium MOF with a MIL-53 architecture. Issue 44 (31st October 2019) - Benecke, Jannik; Mangelsen, Sebastian; Engesser, Tobias A.; Weyrich, Thomas; Junge, Jannik; Stock, Norbert; Reinsch, Helge
Abstract : A new redox active MOF Al-MIL-53-FcDC based on 1, 1′-ferrocenedicarboxylate exhibits reversible electrochemical activity and permanent porosity. Abstract : A metallocene based linker 1, 1′-ferrocenedicarboxylic acid (H2 FcDC) was used to synthesise the first permanently porous ferrocenedicarboxylate, exhibiting a MIL-53 architecture. This compound Al-MIL-53-FcDC [Al(OH)(FcDC)] is obtained in glass vials under mild synthesis conditions at ≤100 °C and after a short reaction time of 90 min. The crystal structure was determined from powder X-ray diffraction data and the compound shows porosity towards N2 and H2 O, exhibiting a BET surface area of 340 m 2 g −1 . Furthermore, the MOF was characterised via EPR and Mössbauer spectroscopy. The Mössbauer spectrum of Al-MIL-53-FcDC shows a characteristic doublet with an isomeric shift of 0.34 mm s −1 and a quadrupole splitting of 2.39 mm s −1, proving the persistence of the ferrocene moiety. A negligibly small amount of impurities of ferrocenium ions could be detected by EPR spectroscopy as a complementary technique. Cyclic voltammetric experiments demonstrated the accessible redox activity of the linker molecule FcDC 2− in Al-MIL-53-FcDC. A reversible oxidation and reduction signal (0.75 V and 0.64 V, respectively, vs. Ag) of FcDC 2− was observed and maintained during forty CV cycles, while the crystallinity of the MOF remained unchanged after the experiment.